2016
DOI: 10.1007/s10902-016-9745-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Strengths Intervention on General and Work-Related Well-Being: The Mediating Role of Positive Affect

Abstract: In this article, we explore the use of strengths interventions, defined as activities and processes that target the identification, development, and use of individual strengths, as an organizational tool to increase employee well-being. Engaging with one's strengths is assumed to be a pleasant activity that elicits positive emotions like joy, pride, and gratitude, which, in turn, contribute to feelings of overall well-being and satisfaction. Building on this assumption, we hypothesized that participating in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 49 publications
6
131
1
7
Order By: Relevance
“…The duration of the interventions varied between overnight implementation (Van Steenbergen et al, 2017), half a day (Meyers & Van Woerkom, 2017) and 12 months (Schelvis et al, 2017;White, Butterworth & Wells, 2017), with seven conducted over 0-4 weeks, 15 over 5-8 weeks, nine over 2-6 months, and four over 6-12 months. The duration of one study was unclear (Coo & Salanova, 2017).…”
Section: Please Insertmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the interventions varied between overnight implementation (Van Steenbergen et al, 2017), half a day (Meyers & Van Woerkom, 2017) and 12 months (Schelvis et al, 2017;White, Butterworth & Wells, 2017), with seven conducted over 0-4 weeks, 15 over 5-8 weeks, nine over 2-6 months, and four over 6-12 months. The duration of one study was unclear (Coo & Salanova, 2017).…”
Section: Please Insertmentioning
confidence: 99%
“…The JD-R model does not state a causal relationship between well-being and engagement, however, some studies observed such a relationship statistically. Imamura et al (2015) found that positive change in depression partially mediated between a psychoeducational online intervention and work engagement at both three and six months post-intervention and Meyers and Van Woerkom (2017) found that positive affect mediated between personal resource building and work engagement as well as life satisfaction and reduced burnout. One study also observed that improved daily vigour mediated between a daily respite intervention and post-intervention vigour (Steidle, Gonzalez-Morales, Hoppe, Michel, & O'Shea, 2017).…”
Section: Mediators Of Work Engagement Interventionsmentioning
confidence: 99%
“…Other inventions made in organizations have shown positive effects and that is an incentive to think that it is possible to generate positive changes in the company [14] [15].…”
Section: Happiness Intervention At Workmentioning
confidence: 99%
“…Of all interventions referred, only the last one was done in a work context, and it was not mentioned whether there were any differences with respect to its effectiveness in terms of gender. Other inventions made in organizations have shown positive effects and that is an incentive to think that it is possible to generate positive changes in the company (Meyers & van Woerkom, 2016;Salanova, Llorens, Acosta, & Torrente, 2013).…”
Section: Happiness Intervention At Workmentioning
confidence: 99%
“…Dese hace ya una década se especificó que no hay homogeneidad ni acuerdo en los investigadores sobre su definición (Alarcón, 2006) e incluso Seligman insiste en volver a hablar de Bienestar Subjetivo en lugar de felicidad (Seligman, 2016). Pese a esto ha habido acercamientos que nos permiten proponer una conceptualización general y entender que la felicidad es un fenómeno multidimensional que incluye estados afectivos positivos, tiene efectos favorables en el trabajo y la empresa y puede ser gestionada dentro de la organización ( Meyers, & van Woerkom, 2016;Wright & Cropanzano, 2000). Esto en la medida que, a pesar de la adaptación hedónica, existen condiciones favorecedoras de la felicidad en el trabajo ( Salanova, Llorens, Acosta, & Torrente, 2013;Seligman, 2011).…”
Section: Conclusion and Limitationsunclassified